The Great Gut Mimicker: A case report of MIS-C and appendicitis clinical presentation overlap in a teenage patient - Michelle Hwang; Kelsey Wilson; Lisa Wendt; Joshua Pohlman; Emily Densmore; Caitlin Kaeppler; Kyle Van Arendonk; Sarah Yale (BMC, 2021)
Abstract Background Abdominal pain and other gastrointestinal symptoms are common presenting features of multisystem inflammatory syndrome in children (MIS-C) and can overlap with infectious or inflammatory abdominal conditions, making accurate diagnosis challenging. Case Presentation We describe the case of a 16-year-old female who presented with clinical symptoms suggestive of appendicitis and an abdominal computed tomography (CT) that revealed features concerning for appendicitis. After laparoscopic appendectomy, histopathology of the appendix demonstrated only mild serosal inflammation and was not consistent with acute appendicitis. Her overall clinical presentation was felt to be consistent with MIS-C and she subsequently improved with immunomodulatory and steroid treatment. Conclusions We note that MIS-C can mimic acute appendicitis. This case highlights MIS-C as a cause of abdominal imaging with features concerning for appendicitis, and MIS-C should be considered in the differential for a patient with appendicitis-like symptoms and a positive COVID-19 IgG. Lab criteria, specifically low-normal white blood cell count and thrombocytopenia, appears to be of high relevance in differing MIS-C from acute appendicitis, even when appendix radiologically is dilated.